Test Site for Small Wind Turbines – Technical and Logistical Issues of a Decade-Long Project - Oliva, Rafael (2024)
This work addresses the main results of a test site for small wind turbines (SWTs) located in Patagonia, and the development of the measurement systems involved, including the uncertainties calculations according to applicable IEC standards. Due to market evolution for over a decade, the test systems evolved from battery-charging SWTs to grid-connected units. The test site, developed and managed by state-owned INTI (National Institute for Industrial Technology), was established in 2012 and received support from the local Curtail-Co municipality and other institutions. Since its creation, it has thrived in aiding local manufacturers of SWTs in certifying their machines, providing power-curve measurement facilities, duration testing, and sound emissions testing. It has also provided design recommendations and improvements related to optimizing energy capture and reliability of SWTs.